Sport and exercise medicine's professional project: The impact of formal qualifications on the organization of British Olympic medical services. (October 2014) - Scott, Andrea
This article documents the intended and unintended outcomes of recent organizational change in UK elite sport. Drawing on semi-structured interviews with 14 doctors and 14 physiotherapists who are current members of the British Olympic Association medical and physiotherapy committees, it argues that attempts by managers in sports medicine to create a highly specialized area of practice have created more immediate tensions within and between both professional groups. The first half of the article argues that on the one hand, the introduction of formal qualifications in sports medicine has created opportunities for clinicians to work full-time in sport, created a clearer distinction between specialized and non-specialized practitioners, provided greater access to and involvement in supportive networks and created more formal pathways for those wishing to enter or progress within the field. At the same time, however, an examination of the working relations between current members of the British Olympic Association's medical and physiotherapy committees highlights, in microcosm, the social organization of sports medicine post organizational change. Thus, this article highlights that attempts by higher managerial sports medicine clinicians to achieve professional status have created a fragmented and internally divided sports medicine speciality made up of a diverse set of practitioners at different stages of sports medicine's professional project.